Design of an ultrafast pulsed ponderomotive phase plate for cryo-electron tomography - Du, Daniel X; Fitzpatrick, Anthony (bioRxiv, 2022)
Ponderomotive phase plates have shown temporally consistent phase contrast is possible within electron microscopes via high fluence static laser modes resonating in Fabry-Perot cavities. Here, we explore using pulsed laser beams as an alternative method of generating high fluences. We find through forward-stepping finite element models that picosecond-or-less interactions are required for meaningful fluences phase shifts, with higher pulse energies and smaller beam waists leading to the predicted higher fluences. An additional model based on quasiclassical assumptions is used to discover the shape of the phase plate by incorporating the oscillatory nature of the electric field. From these results, we find the transient nature of the laser pulses removes the influence of Kapitza-Dirac diffraction patterns that appear in the static resonator cases. The addition of a second laser aligned 90 degrees to the first induces anisotropy to the shape of the phase plate. By incorporating a shifting-electron-beam algorithm, the effects of a finite electron beam crossover are also simulated. A total pulse energy of 8.7 microJoules is enough to induce the required pi/2 phase shift for Zernike-like phase microscopy. As a brief thought experiment, we also explore the usage of high frequency lasers in a standard electron emission scheme to see if a pulsed electron beam is even necessary. Ultimately, frequency requirements limit the laser to nanosecond pulse durations, causing the required pulse energies to reach unreasonable levels before adequate phase shifts are achieved. Competing Interest Statement The authors have declared no competing interest.